Variation within MBP gene predicts disease course in multiple sclerosis - Zhou, Y; Simpson, S; Charlesworth, J; Van Der Mei, I; Lucas, R; Ponsonby, A; Auslong Investigators Group; Taylor, B; Dwyer, T (Wiley, 2017)
Objective Prognosis following a first demyelinating event is difficult to predict, with no genetic markers of MS progression currently identified. Myelin basic protein (MBP) is a major component of the myelin sheath of CNS neurons and may play a central role in demyelinating diseases such as MS. However, genetic variation in MBP has not been implicated in MS onset risk in large genome‐wide association studies. We hypothesized that genetic variations in MBP may be a determinant of MS clinical course. Materials and Methods We investigated whether variations in the MBP gene altered clinical course (conversion to MS and/or relapse, and annualized change in disability), using a prospectively collected longitudinal cohort study of 127 persons who had had a first demyelinating event, followed up to the 5‐year review. Results We found one variant, rs12959006, predicted worse clinical outcomes. The risk genotype (CT + TT) was significantly associated with hazard of relapse (HR = 1.74, 95% CI = 1.19–2.56, p = .005) and of greater annualized disability progression (β = 0.18, 95% CI = 0.06–0.30, p = .004). We also found a significant interaction between the risk genotype and baseline anti‐HHV6 IgG in predicting MS (pinteraction = 0.05) and relapse (pinteraction = 0.02). Functional prediction analysis showed this variant is the target of many transcription factors and the binding sites of miR‐218 and miR‐188‐3p. Conclusions Our results provide novel insights into the role of genetic variation within the MBP gene predicting MS clinical course, both directly and by interaction with known environmental MS risk factors.